Spectrophotometric characterization of simple glazings for a modular façade - Sacht, H. M. (2016)
A large variety of transparent materials is available for uses in buildings façades and all glazing properties must be considered in their choice. Such a selection should be a careful process of evaluation and weighing of tradeoffs. The correct glazing specifications for façades can reduce energy consumption in buildings, because the heat exchange and passage of radiation into the building as light and heat occur through transparent surfaces. Therefore, glazing significantly contributes to the heat transfer between outdoor and indoor spaces, which act directly on daylighting and thermal comfort. This manuscript addresses a spectrophotometric characterization of glazings for the study of components for the design of a modular façade system based on the climate of Portugal. The study focused on results of spectrophotometric measurements of an optical behavior in different solar spectrum intervals (ultraviolet, visible and near infrared), specifically the transmittance of some types of simple glazings. The results show the percentage of transmission to spectrum intervals, which enabled the analysis (OK?) of the efficiency of the glazing regarding daylighting and correlation to the thermal performance. Indications for specifications and adequate uses based on transmission of transparent surfaces have been obtained and complemented the datasheets available from the manufactures.